Antihyperuricemic Potential of Syzygium polyanthum: A Systematic Review - Feby Anastasya Sirait; Nasywa Zahirah Yustin (Institute of Advanced Knowledge and Science, 2026)
Hyperuricemia is a common metabolic disorder that increases the risk of gout and other chronic diseases. Syzygium polyanthum has long been used in traditional medicine to reduce uric acid levels, but the available evidence has not been systematically reviewed. This study aimed to summarize the current evidence on the antihyperuricemic activity of S. polyanthum. A systematic literature search was conducted in ScienceDirect, Google Scholar, Garuda, and the Directory of Open Access Journals (DOAJ) for articles published between 2010 and July 2026. Study selection followed the PRISMA 2020 guidelines. Fifteen studies met the inclusion criteria, consisting of eight in vivo studies, four clinical studies, two in vitro studies, and one in silico study. Most studies reported that S. polyanthum significantly reduced serum uric acid levels, and several experimental studies showed activity comparable to allopurinol. The in vitro studies also demonstrated xanthine oxidase inhibitory activity, suggesting that this enzyme is one of the main therapeutic targets. The antihyperuricemic effect was mainly associated with flavonoids and phenolic compounds present in the leaves. However, differences in extraction methods, dosages, and study design limited direct comparison between studies. Overall, the available evidence suggested that S. polyanthum may serve as a potential natural antihyperuricemic agent, although further well-designed clinical studies are still needed.